Cara Human Resources Development (HRD) Melakukan Perekrutan dan Seleksi Crew Kapal Offshore pada PT. Alfa Arafah Crewing Jakarta - Dafid Ginting; Ananda Amroh; Taruna Taruna (Departement of Mathematics Education, 2024)
PT. Alfa Arafah Crewing Jakarta is a shipping company that operates in the field of ship crewing. Ship crewing is a service carried out on behalf of foreign sea transportation companies or national sea transportation companies. The ship's crew is an object in the process of activities on board the ship, so the process of recruiting and selecting prospective new ship's crew must be planned carefully so that the recruitment and selection of ship's crew is carried out as expected. The purpose of this research is to find out how Human Resources Development (HRD) carries out recruitment and selection of offshore ship crew at Pt. Alfa Arafah Crewing Jakarta. This research uses a qualitative descriptive method by describing in detail the implementation of the quality-based crew recruitment and selection process at PT. Alfa Arafah Crewing Jakarta. Apart from that, data collection was carried out using interviews, observations, book literature and documents on ship crew selection process activities at PT. Alfa Arafah Crewing Jakarta. The research results show the obstacles faced by PT. Alfa Arafah Crewing Jakarta in recruiting and selecting Offshore vessels. PT. Alfa Arafah Crewing Jakarta is that the implementation of the ship crew selection process has not been well organized. Because the crew's requests must be in accordance with the client's needs. Efforts have been made to overcome obstacles to the implementation of the crew recruitment and selection process at PT. Alfa Arafah Crewing Jakarta is that prospective crew members should meet the company's qualifications by having the skills and certification required by the client to build good performance on board the ship.